A correlation and path analysis of seed yield and yield contributing characters in safflower (Carthamus tinctorius L.): A correlation and path analysis of seed yield and yield contributing characters in safflower (Carthamus tinctorius L.) - MUKTA MANE; V N WANI; L N TAGAD (Journal of Oilseeds Research, 2023)
Correlation and path analysis were carried out to determine the effect of various traits as components of seed yield in 34 safflower genotypes. The genotypes were evaluated in RBD with three replications during Rabi 2021, at the central research farm of the Department of Genetics and Plant breeding at Sam Higginbottom University of Agriculture, Technology, and Sciences in Prayagraj. The analysis of variance exhibited significant difference for all the characters suggesting the presence of inherent genetic variations among the genotypes. Correlations among the traits revealed that the Harvest index and seed yield/plant had a positive and substantial correlation. Harvest index, seed index, number of seeds/capitulum, and number of capitula/plant were discovered by path analysis at the phenotypic level as essential direct components for seed yield/plant.